Investor attention and stock market performance during Covid-19 pandemic: evidence from Malaysia - Chan, Shu Wen; Lee, Jia Yong; Lee, Li Peng; Tiu, Phei Xin (2021)
In this research, we indicate the relationship of investor attention proxied by Google Search Volume Index (GSVI) and Malaysia Stock Market Performance on Covid-19 pandemic. Since the Covid-19 pandemic is a new phenomenon, it has led to the first financial crisis contributed by the pandemic in history. In this study, search queries of “Coronavirus” and “Covid-19” is indicated. Results revealed that keyword “Coronavirus” has no insignificant results to the Kuala Lumper Composite Index (KLCI) performance and keyword “Covid-19” is tested to be significant to indicate the relationship between investor attention and the Malaysia stock market performance. To indicate the validity of the regression model, various test like Augmented Dickey-Fuller test, Philips-Perron test, Breusch-Godfrey LM test, Jacque-Bera test, White heteroscedasticity test has been carried out in this research project. The results had revealed that the model have no existence of unit root, autocorrelation and heteroscedasticity problems in the model and the error term is normally distributed. Granger causality test has been carried out and results that three dependent variables have no granger causal relationship with GSVI Covid-19. To indicate the short and long run effect on the model, Impulse Response Function has been carried out and proven that there have no impacts on the both short and long runs between the dependent variables and GSVI Covid-19. This study found out that insignificant relationship between investor attention proxied by GSVI with stock market return and stock market volatility. The empirical results support efficient market hypothesis (EMH) which stated that the Malaysian stock market is efficient and hence, there is no arbitrage opportunities for investors since stock prices fully reflect all information.